Exploring relationships among students' computational thinking skills, emotions, and cognitive load using simulation games in primary education. - Pellas, Nikolaos (Journal of Computer Assisted Learning, 2023)
Background: Owing to the exponential growth of three‐dimensional (3D) environments amongst researchers and educators to create simulation games (SGs) in primary education, there is a growing interest to examine their potential support in computer science courses instead of visual programming environments. Objectives: This study explores the relationships between students' learning performance, focusing on computational thinking (CT) and programming skills development, in association with their cognitive load (mental load and mental effort) and emotions (happiness, anger, anxiety, sadness) by playing SGs. Methods: A total of two hundred and ninety participants (n = 290) in fifth‐grade classes (10–11 years old) of Greek primary schools completed all pre‐and post‐intervention tests. A quasi‐experimental study was conducted over a 14‐week timetable course and in two comparison conditions, in which a SG was created by using OpenSimulator&Scratch4SL and Scratch for the experimental group (n = 145) and the control group (n = 145), respectively. To further investigate the effectiveness of the proposed SG in each teaching intervention, an exploration of relationships between students' learning performance, cognitive load, and emotions through multiple analyses, depending on correlation, t‐tests, correlation, and hierarchal regression was delivered. Results and Conclusions: The findings indicate that the proposed SG created by using OpenSimulator&Scratch4SL positively affected students' emotions and cognitive load, whereas there was no significant difference in learning gain between the two groups. Implications: The study provides empirical evidence on the effects of SGs on students' knowledge acquisition, highlighting the importance of considering both cognitive and emotional components in the design of these games. The findings also offer valuable insights for implications policy and practice. Lay Description: What is already known: Interactive environments can support the development of students' computational thinking (CT) and programming skills due to a wide range of digital elements/features that expand the boundaries where learning can happen.CT is a 21st‐century skill to be on top with others, such as reading, writing, and arithmetic for future generations of students to tackle real‐life problems.Despite a broad consensus on the increasing number of interactive environments, there is no dedicated measurement of their effects on students' performance and their possible association with psychological constructs. What this paper adds: This study explores any possible relationships amongst students' CT skills, emotions, and cognitive load for programming courses in fifth‐grade (10–11 years old) classes of primary education by playing a simulation game (SG).The proposed SG was created by using two interactive environments that project different 2D/3D user interface and game elements (e.g., special effects, scenes, animations, feedback, challenges, goal clarity, and scripted interaction).A quasi‐experimental study was conducted over a 14‐week timetable course and in two comparison conditions, in which the proposed SG was created by using OpenSimulator&Scratch4SL and Scratch for the experimental group (n = 145) and the control group (n = 145), respectively. Implications for practice and/or policy: In‐game scenario and students' embodied experiences can increase CT vocabulary acquisition, understanding, and expression of solution plans via visual coding.A practical roadmap for practitioners and instructors proposed how to purposefully integrate elements/features into interactive environments.Problem‐solving exercises in a simulated reality can become interesting and reduce students' cognitive load, when they are taking part in enjoyable and playful settings.